2019
DOI: 10.2340/16501977-2583
|View full text |Cite
|
Sign up to set email alerts
|

The World Health Organization Disability Assessment Schedule (WHODAS 2.0) and the WHO Minimal Generic Set of Domains of Functioning and Health versus Conventional Instruments in subacute stroke

Abstract: LAY ABSTRACTThis study compared short generic International Classification of Functioning, Disability and Health (ICF)based measures of functioning, the patient-and proxyreported 12-item World Health Organization Disability Assessment Schedule (WHODAS 2.0) and the 7-item WHO Minimal Generic Set of domains of functioning and health assessed by a neurologist, with traditionally used measures of stroke in the subacute phase. Although proxies rated 6 out of 12 separate WHODAS functions more impaired than did the p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
21
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(25 citation statements)
references
References 30 publications
1
21
0
1
Order By: Relevance
“…Besides, inadequate health care services were also significant contributors to the disability problem on the continent [17]. Similarly, this study reported a very small proportion of PwDs employed in the government -both in urban and rural areas -and a significant majority of them were involved in small-scale farming with strained livelihoods.…”
Section: Discussionmentioning
confidence: 51%
See 2 more Smart Citations
“…Besides, inadequate health care services were also significant contributors to the disability problem on the continent [17]. Similarly, this study reported a very small proportion of PwDs employed in the government -both in urban and rural areas -and a significant majority of them were involved in small-scale farming with strained livelihoods.…”
Section: Discussionmentioning
confidence: 51%
“…The household survey questionnaire included items from The World Health Organization Disability Assessment Schedule (WHODAS 2.0), International Classification of Functioning, Health and Disability (ICF) and MedicalOutcomes Study-Short Form (SF-36) tools, which were adapted based on local context and translated into the local language -Amharic. WHODAS 2.0 is standardized and validated tool to assess health and disability status both at individual and population levels, and across cultures[17]. As a generic tool, it is effective to assess activity limitations and participation-restriction due to disability in daily lives of individuals both at population and clinical set-up.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, it was pre-tested on a population with similar demographic and socioeconomic pro le as the study area, with its outcomes used to review and adapt its framework, organization as well as items sequencing and wording. WHODAS-2.0 is a standardized and validated tool to assess health and disability status both at individual and community levels, and across cultures [19]. As a generic tool, it effectively assesss disability induced limitations on activity and participation both in community and clinical set-up.…”
Section: Data Collection: Tools and Proceduresmentioning
confidence: 99%
“…As a generic tool, it effectively assesss disability induced limitations on activity and participation both in community and clinical set-up. Furthermore, it has been fruitfully deployed to measure the effectiveness of disability interventions [19]. The survey questionnaire speci cally adapted items from WHODAS-2.0 that measure the six domains of disability: learning and intellectual, mobility, self-care, getting along, life activities and participation.…”
Section: Data Collection: Tools and Proceduresmentioning
confidence: 99%